Penggunaan Obat Tradisional Oleh Masyarakat di Kelurahan Tuah Karya Kota Pekanbaru - RATNA SARI DEWI (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2019)
The use of traditional medicine continues to increase and has been used widely as an treatment. Not only concoction itself, traditional medicinal products today have been widely circulating. his study aims to obtain an overview of the use of traditional medicine Kelurahan Tuah Karya Pekanbaru City. The type of research used is descriptive observational research with cross sectional design. The selection of respondents was conducted by non random sampling with a purposive sampling technique and obtained as many as 168 respondents. The instrument used was a multiple choice sheet with six categories of questions. The description of traditional drug use obtained, namely the type of traditional medicine used by the community is herbal medicine (52.38%), with the reason that the community uses traditional medicine because it is made from natural ingredients (37.50%) and sources of information obtained from print media electronics (47.62%), the place to obtain traditional medicines from the pharmacy (64.29%), the most common type of disease is colds (37.50%) and the dosage forms that are mostly used are fluids (92.86%)